Exploring the potential of designing automated content builder for mobile apps using evolutionary computing methods - Chin, Kim On; Jason Teo; Rayner Alfred; Lau, Hui Keng; Mohd Hanafi B. Ahmad Hijazi; Norhayati Daut; Chang, Kee Tong; Yap, Khong Lim; Gabriel Jong Chiye; Teo, Kein Yau; Kung, Ke Shin (Universiti Malaysia Sabah, 2014)
The lack of good quality games on the Android Market has led this project to be a starting platform to learn about game development, and to design and develop a simple 3D third-person shooting game. The project has three objectives. The first is to create a 3D game environment with a third-person camera view on the Android platform, which can be achieved using a game engine known as the jMonkey Engine. The second is to implement the accelerometer - a commonly built-in feature of Android smartphones - as a viable control method for such a game. Finaly, a finite state machine will be implemented for the game AI, and designed such that it will provide a challenge to players.